2007
DOI: 10.1002/hfm.20077
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of an augmented reality welding helmet

Abstract: The article describes the development and ergonomic evaluation of an augmented reality (AR) welding helmet. The system provides an augmented user interface with supporting information relevant to the welding process. The experimental studies focused on hand-eye coordination of welders and nonwelders with two prototypes of the augmented reality welding helmet. The first prototype operated at 16 frames per second, whereas the second, improved version had 20 frames per second. In addition, the hand-eye coordinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The second domain focuses on application of AR technology in diverse scenarios, for example in industry [7,3,6]. A third domain examining user related aspects including psychological and medical questions is the most important for this paper.…”
Section: Related Workmentioning
confidence: 99%
“…The second domain focuses on application of AR technology in diverse scenarios, for example in industry [7,3,6]. A third domain examining user related aspects including psychological and medical questions is the most important for this paper.…”
Section: Related Workmentioning
confidence: 99%
“…An improvement in time for welding processes was reported by Echtler et al (2004) when an AVS was used versus a traditional welding helmet. However, Park et al (2007) reported contrary effects like a longer time‐on‐task when comparing an AVS attached to the welding helmet with traditional welding performed by both skilled welders and untrained participants.…”
Section: Related Workmentioning
confidence: 99%
“…Except for the study by Park et al (2007), all aforementioned studies of AVS for the shop floor indicated either a decrease in time‐on‐task (Echtler et al, 2004; Wiedenmaier, 2004; Wiedenmaier et al, 2003) or an increase in accuracy of task processing (Meyer Steil, & Müller, 2005; Tang et al, 2004). However, these studies were carried out with either monocular or biocular HMDs, presenting two‐dimensional virtual objects within the field of view.…”
Section: Related Workmentioning
confidence: 99%
“…One is integrating AR with manual gas-metal-arc welding technology. Since in the traditional manual gas-metal-arc welding, the welder has a very limited field of view through the dark cartridge used to protect welders' eyes from dangerous UV radiation, Park (2007) applied the AR registration technology to welding helmet to aid welding process by virtually presenting the outline of to-be-welded objects. Based on it, they developed an AR-based welding helmet system ---TEREBES (Tragbares Erweiter tes Realitäts-System zur Beobachtung von Schweißprozessen System), a wearable Augmented Reality System for observation of welding processes.…”
Section: Augmented Reality In Assemblymentioning
confidence: 99%